Rake task management essentials: deploy, test, and build software to solve real-world automation challenges using Rake - Koleshko, Andrey (Community expertise distilled., 2014)
Rake is a build automation tool written in Ruby. It allows you to specify tasks and describe dependencies as well as group tasks in a namespace. Rake uses Ruby's anonymous function blocks to define various tasks, allowing the use of the Ruby syntax. Rake's goal is to automate build processes quickly and expressively. "Rake Task Management Essentials" is a practical guide that covers the latest techniques in building, testing, and debugging rake tasks to solve real-world automation challenges. The book starts with a basic knowledge of Rake, allowing you to solve repetitive tasks. Then it provides you with information about processes performed with files, which is crucial for understanding the application of the tool. It includes demonstrations to show you how tasks can be run in parallel and how they can be applied in practice. Thereafter, it integrates Rake with Ruby with the help of simple and clear examples. By the end of this book, you will know how Rake has changed the programming world, especially in the Ruby community.